Towards resolving the problematic status of the digenean genus Astiotrema Looss, 1900: An updated concept and revision of species composition for Astiotrema (sensu stricto) - Karar, Yasser F. M.; Blend, Charles K.; Dronen, Norman O.; Adel, Asmaa (Zootaxa, 2021)
Species of Astiotrema Looss, 1900 (sensu lato) infect a wide range of fishes, amphibians and reptilians. They also possess a considerably wide spectrum of morphological features. Several species were recognized for variable, confusing, overlapping and unspecialized morphological characters rather than for unique distinguishing features, causing continuing dispute around the validity of several species. Following comprehensive review, a revised restricted concept of Astiotrema is proposed including a morphologically strict definition. Both Tremiorchis Mehra & Negi, 1926 and Astioglossimetra Bilqees, Khatoon & Khan, 2002 are synonymized with Astiotrema (sensu stricto). Several nominal species are synonymized, others are excluded and characters for each recognized species are presented and explained. Only eight species are recognized: Astiotrema cyclemysi Siddiqi, 1965, Astiotrema emydis Ejsmont, 1930, Astiotrema fotedari Dhar, 1977, Astiotrema impletum (Looss, 1899) Looss, 1900, Astiotrema karachiensis (Bilqees, Khatoon & Khan, 2002) n. comb., Astiotrema odhneri Bhalerao, 1936, Astiotrema ranarum (Mehra & Negi, 1926) Fotedar, 1971 and Astiotrema reniferum (Looss, 1898) Looss, 1900. A key to the species of Astiotrema (sensu stricto) is presented, a comprehensive list of all host-locality records is included and host-parasite specificity is elucidated.